In Vitro Propagation of Jasminum Sambac L. - Faizy, Waad S.; Nooh, Khawlah Mahmood Al; Al-Zuhairi, Faris F. A. (American Journal of Botany and Bioengineering, 2025)
To obtain highly locally desired Iraqi jasmine (Jasminum sambac L.) seedlings in a large scale and free of pathogens to meet the local demand for this plant, this work was done in the Laboratory for Plant Cell and Tissue Culture/Department of Plant production techniques/Agricultural Technical College/Northern Technical University. Included In vitro planting of jasmine single nodes during the multiplication stage on MS (Murashige and Skoog) basal medium enriched by (0, 0.5, 1, 1.5, and 2.0 mg L-1) of BA and Kin. At the rooting stage, the plantlets that obtained were planted on full and half of MS salt’s strength medium enriched with IBA at a concentration of (0, 0.5, 1, 1.5, and 2 mg L-1). The results showed that the shoot numbers were not affected significantly by CK type. In contrast, the number of leaves was significantly affected, as nodes were planted in media containing Kin recording the largest leaves number (6.24 leaf/shoot) compared to those planted in media containing BA. While, the nodes planted on MS nutrient medium equipped with (1 mg L-1) BA gave the largest new shoots formed number and the greatest number of leaves (2.6 and 7.40 respectively) with significant superiority over all other treatments. As for the rooting stage a highest rooting percentage (80%) and the largest roots number (4.8) was recorded in MS with half salt’s strength medium enriched by 0.5 mg L-1 IBA, the plantlets were successfully transferred to the greenhouse with a survival percentage of (85%). The results of the study can be adopted as a successful protocol for the propagation of the high aesthetic value Razaki plant used as an ornamental plant.